Diagnosing Soil and Coconut Root Existence in Lontang Plantation of Manado City - Tamod, Zetly Estefanus; Kumolontang, Wisje; Kaunang, Djony (UNIVERSITY OF LAMPUNG, 2016)
Province of North Sulawesi has been known as wave palm area (coconut). One of the plantations (coconut) potential become the farmer’s income and Locally-Generated Revenue (LGR). Therefore, it is important to maximize the soil function and root system of coconut. This research was aimed to diagnose a soil and coconut root existence in Lontang Plantation of Manado City. Soil observations were carried out on a single stretch of coconut plantations owned by community. The observation was done through the soil profile at a spacing of <1 m; 3 m and 5 m from the main tree of the coconut. The results showed that decreasing of C-Organic content in 1 m depth was not followed by enhancement of soil content weight, because C-Organic has spread equally in middle state and into the depth of >1 m on 3 and 5 m spacing profile from the main tree which categorized as low. Existence of total root length (Lrv) and dry root weight (Drv) shows that deeper soil will be more reduced of the root Lrv and Drv values along with the organic material in the bottom layer (> 1 m) lower than above it. The highest Lrv and Drv average value is located on the depth of 0 – 60 cm. Specrol existence on 1 - 3 m spacing profile have showed many soft roots which grow on these spacing. The soft root has a roles to absorb nutrient and water for the plant and direct contact with the soil.